Indicators of governance of marine ecotourism resources: perception of communities in Pulau Perhentian, Terengganu - Mohd Noh, Aswani Farhana; Shuib, Ahmad; Tai, Shzee Yew; Mohd Noh, Kusairi (Universiti Malaysia Sarawak, 2018)
To be effective, the establishment of the Marine Protected Areas requires support from various stakeholders, which are directly or indirectly affected by the establishment. The support of relevant agencies to manage the Marine Protected Areas may depend on how the communities perceive the benefits of the establishment. The objective of this paper is to present the results of an analysis on the perception of local communities on the governance of the Marine Protected Areas by the relevant agencies. Data for the study were collected from members of the local communities on Pulau Perhentian using face-to-face interviews. The results show that most members of these communities were aware of the establishment of the Marine Protected Areas, though some were doubtful of the actual benefits of the establishment. Communities on Pulau Perhentian, which were directly dependent on the marine resources for their ecotourism-related businesses, were quite apprehensive of the ability of relevant agencies to act on reducing the encroachment of fishers in protected zones. Generally, the local communities agreed that the relevant agency were doing a good job of enforcing rules and regulations to protect the resources in the marine ecosystem. The cooperation among the stakeholders in adapting to the norms of governance was perceived as helpful in affecting the management of Marine Protected Areas.